Consequences of Floods and Permafrost Degradation for Life Support System of Population of Alazeya River Basin (Second Half of 20th—21st Centuries) - A. A. Suleymanov (Научный диалог, 2022)
Based on the analysis of archival data, published scientific literature and author’s field materials, the consequences of the degradation of “permafrost” for the life support system that has developed in the village of Argakhtakh, Srednekolymsky ulus of the Republic of Sakha (Yakutia) are analyzed. To increase the representativeness of the overall picture, the transformations that have taken place are considered on the example of two cases: natural disasters during the period of a relatively stable state of the environment, on the one hand, and serious climate changes that have already occurred in recent decades. The causes, course and consequences of the 1977—1978 flood are considered. It was noted that it caused significant damage to agriculture, but the village itself was practically not affected. The floods that occurred in 1997, 2007—2008 and 2017—2018 had more serious consequences for the life support system of Argakhtakh. A significant role in their genesis played the degradation of permafrost, intensified due to an increase in the average annual air temperature and anthropogenic impact. As a result of floods, not only farmlands were flooded, but a new channel of the Alazeya River arose, a local fur farm was deprived of a stable land connection with the village, damage was caused to Argakhtakh’s housing stock, outbuildings and infrastructure facilities. It has been established that this has led to a radical reduction in the scale of the local population's employment in traditional sectors of economic activity, the elimination of fur farming, the deterioration of the transport accessibility of the village, and the costs of the population for the restoration of households.